Pemberdayaan Remaja Pedesaan melalui Integrasi Bimbingan Karier dan Modifikasi Perilaku: Model Intervensi Konseli Berbasis Komunitas di Desa Teluk Kenidai - Donal; Fadhila Rahman; Isnaria Rizki Hayati; Kiki Mariah; Dwi Rahmadani Indra; Elni Yakub; Sri Dasweni; Dian Oktari (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
Rural adolescents often face limited access to guidance and counseling services, particularly in career planning and the development of adaptive behaviors, amid rapid societal and labor market changes. This article presents a community-based counseling intervention model integrating career guidance, behavior modification, and experiential learning to empower rural youth. The model is based on the implementation of the Community Counseling and Outbound Service Program (KOMANDO) 2025 conducted by Universitas Riau in Teluk Kenidai Village, Indonesia. The program involved students from SMP Satu Atap Teluk Kenidai and spanned four stages: community needs assessment, career exploration, behavior modification through educational games, and reflection and evaluation. Data were collected through participatory observation, participant feedback, and reflective discussions without employing an experimental design or standardized psychometric measures. Observational findings indicated improved self-awareness, increased interest in career exploration, and active participation in collaborative learning activities that promoted teamwork and responsibility. Participants responded positively to the play-based experiential learning approach, suggesting its potential to foster adaptive behaviors, although no causal conclusions can be drawn. This article proposes the Community-Based Career Counseling Empowerment (CBCCE) Model, which integrates community context, needs assessment, career guidance, behavior modification, and experiential learning into a sustainable framework for empowering rural youth. The model offers practical implications for expanding counseling services through collaboration among schools, universities, and local governments.